O livro de cabeceira de Peter Greenaway: silêncio, som, palavra, prazer, personagem - Jaider Fernandes Reis (Argumentos, 2023)
The present work proposes to present the film The Pillow Book, by British director Peter Greenaway. Inspired by a tenth-century Japanese literature classic, the director builds a narrative that highlights the relationships between text, image and sound to address topics such as art, pleasure, sex, literature and writing.The purpose of this article is to present the work and highlight elements used by Greenaway in his audiovisual narrative: the image, which was called here the book of silence; music, called the book of sound; and writing, called the book of words; intertextuality, called the book of pleasure; the construction of the character, called the book of women-characters. This choice was made to pay homage to the way in which the director resumes references to Sei Shonagon's diary in the film. Although it is a filmfrom 1996, it is necessary to point out that it is current, either because of the multiple screens used to compose a complex narrative, or because of the themes addressed in the plot.